Multidrug-resistant Escherichia coli in a canine patient with urinary tract infection (FAVE Sección Ciencias Veterinarias, 2025)
Urinary tract infections in dogs are commonly caused by bacterial colonization, particularly Escherichia coli. In recent years, the prevalence of multidrug-resistant strains has increased, posing a significant challenge to both patient and public health. This report presents the case of a male dog diagnosed with a urinary tract infection (UTI) exhibiting hematuria, pollakiuria, and hematological alterations, including leukocytosis and neutrophilia. Urine culture confirmed the presence of E. coli, and susceptibility testing revealed resistance to multiple antibiotics, including ceftriaxone, cefazolin, cefaclor, cefalexin, cefuroxime, amoxicillin with clavulanic acid, ciprofloxacin, and imipenem, the latter being a last-resort antibiotic in human medicine. This finding underscores the growing concern antimicrobial resistance in companion animals, as it limits therapeutic options and represents a potential zoonotic risk. The detection of such resistance is particularly relevant given the role of dogs as reservoirs of resistant bacteria that can be transmitted to humans. This highlights the need for ongoing surveillance to safeguard both animal and public health.
Keywords: Escherichia coli; urinary tract infections; antibiotic resistance; imipenem; public health